Projeto de vida do adolescente institucionalizado o caso: a Fazenda do Menor - Macêdo, Edna Lucia do Nascimento (2006)
This research has intended to analyse the life-project of teenagers facing the process of institutionalisation of Fazenda do Menor, in Feira de Santana-BA. Working with a study of case, it assumes the theoretical statement that building a life-project teenagers reinforce the EGO, grow up the self-regard and give sense to the life. To data collection were used participant observation and interviews, instruments we consider very important in order to examine accurately some questions and to provide closeness with the subject. The results have shown that teenagers, even living under the institutionalisation process, could make their life-projects. Some projects include modest aspirations, but most of them are realists and involve a wider perspective. Through this construction the teenagers make evident that to study is the way to substantiate their life-project.